Considerações Éticas sobre o Centro de Atenção Psicossocial no contexto cearense: o olhar do supervisor clinico institucional - Lemos, Patrícia Mendes (2012)
The research deals with the suffering and mental illness at the Center for Psychosocial Care (CAPS) and its ethical ramifications. Amid the demands and subjective productions of a social context understood as late-modern, which we named as a late-modern demands in Mental Health, this device takes responsibility for understanding, care and treatment of a subject historically excluded by its relationship with madness, establishing itself as the place par excellence for the care of the other-otherness. We set the following assumptions: 1) there is an ethic that subsidizes specific practices of Mental Health developed by CAPS, 2) the demands of late-modern mental health are made in relation to the socio-historical context and 3) this context produces specific ways of distress and mental illness. Given this, we were encouraged to achieve an understanding of the ethical dimension in CAPS, reaching the primary question: What is the relationship between the ethical dimension present in the CAPS and the demands of late-modern mental health? During the contact with the otherness of the texts of authors who have given theoretical support to the study as well as with the difference element seen in the discourses / texts of the respondents, we found that the ethical dimension could not be understood, unless in the uniqueness and complexity of its relationship with the demands. As a result, we adopt the general goal: to understand the ethical dimension in Psychosocial Care Center on its relationship with the late-modern demands in Mental Health. And we also take specific objectives: to characterize the late-modern demands in Mental Health from the horizons presented by CAPS supervisors and understand the ethical dimension in their relationship with the CAPS in the practice of clinical-institutional supervision. Faced with the aspiration to capture understanding dimensions about the theme, we chose the philosophical hermeneutics of Hans-Georg Gadamer as a methodological possibility, through the process of fusion of different horizons presented, as well as the elements of otherness and history hidden in the texts / discourses. The choice of supervisors of CAPS, as the possibility to access the practice and reflection that pervade the reality of these devices, due to the fact that these subjects occupy an external position (they do not act directly in contact with users through therapeutic unlike the technical), as well as its primary function of inquiry and intervention, which ultimately aims to comply with the ethical-political principles that the CAPS advocate in line with the objectives of the Mental Health Reform. We then conducted seven semi-structured interviews, which served for the interpretive philosophical exercise. The issues raised and the elements to our understanding constitute a tripod of analysis, whose result was condensed into specific themes, which are revealing of the objectives pursued in relation to the ethical dimension of the CAPS. These themes shaped: aspects of ethics and the ethical limits of the system of Mental Health, the late-modern demands and ethical requirement of the other, and the place of ethics in the Psychosocial Care Center. Running along a pertinent discussion on the place of suffering and mental illness in CAPS, its inseparable relationship with the socio-historical context and the complexity of issues that involve ethical dimensions, we point out the radical Levinasian ethics as a parameter, from which the practices of mental health could be rethought and reinvented in order to reach the most relevant answers and consonant with the magnitude of the other-alterity, whose presence imposes so irresistible to the actors who participate in a process of change in permanent construction.